Genetic line-specific immune profiles and immunometabolic responses to intramuscular lipopolysaccharide injection - Elmore, Kayla M.; Lamont, Susan J.; Bobeck, Elizabeth A. (Frontiers in Immunology, 2025)
Previous research has investigated highly inbred chicken genetic lines from a metabolic, immune response, genetic profile, and immune trait standpoint, including response to lipopolysaccharide (LPS). Fayoumi lines (M5.1, M15.2) are known for their resistance to bacterial and viral infections, while Leghorn lines (Ghs6, Ghs13) display lower disease resistance. Results highlighted a need to increase LPS dose above initial work using 1mg/kg bodyweight (BW). Therefore, this study investigated the immune profiles and metabolic phenotypes of peripheral blood mononuclear cells (PBMC) from highly inbred genetic lines under resting and stressed metabolic states. Fifty-four adult birds from 5 highly inbred genetic lines (M5.1, M15.2, Ghs13, Line-8, and Sp-21.1) were randomly assigned to 0.9% sterile saline control or 2.4 mg/kg BW intramuscular LPS (Escherichia coli O55:B5). BW was recorded at baseline before injection and 24 h post-injection (hpi). Cloacal temperature was recorded at baseline, 2 hpi, and 24 hpi, while blood was collected for flow cytometry and metabolic analysis. Data were analyzed using the SAS 9.4 MIXED procedure with genetic line, injection status, and interaction as fixed effects, with significance at p ≤ 0.05. Baseline immune cell profiles varied by line (p ≤ 0.001). At 2 hpi, LPS did not impact BW or temperature, but influenced all queried immune cell populations while decreasing ATP production and glycolytic rates (p ≤ 0.02). At 2 hpi, M5.1, Line-8, and Sp-21.1 LPS-inoculated birds had increased circulating CD3+ cells (51.8-62.3%, p ≤ 0.0001). LPS decreased CD3+CD1.1+ cell levels by 34.1% at 2 hpi (p ≤ 0.0001). M5.1, M15.2, and Line-8 controls had 14.9-66.5% higher CD3+CD4+ levels than LPS-inoculated birds, while CD3+CD4+ cells were 12.2% lower in Ghs13 post-LPS (p ≤ 0.0001). CD3+CD8α+ populations increased 41.1-63.2% in all LPS-injected birds at 2 hpi, except Ghs13 (p ≤ 0.0001). These results highlight genetic line-specific immune responses to LPS. By 24 hpi, immune profiles and glycolytic rates were largely recovered from LPS, while genetic line effects persisted, indicating line-specific immune responses (p ≤ 0.04). Further understanding cellular preference and metabolic switching during inflammatory challenges could provide insight into how to best support and optimize bird performance during the production cycles.